Single-dose oral anti-arrhythmic drugs for cardioversion of recent-onset atrial fibrillation: a systematic review and network meta-analysis of randomized controlled trials. Issue 8 (16th March 2021) - Ibrahim, Omar A; Belley-Côté, Emilie P; Um, Kevin J; Baranchuk, Adrian; Benz, Alexander P; Dalmia, Shreyash; Wang, Chang N; Alhazzani, Waleed; Conen, David; Devereaux, P J; Whitlock, Richard P; Healey, Jeff S; et al.
Abstract: Aims: Single oral dose anti-arrhythmic drugs (AADs) are used to cardiovert recent-onset atrial fibrillation (AF); however, the optimal agent is uncertain. Methods: We performed a systematic review and network meta-analysis of randomized trials testing single oral dose AADs vs. any comparator to cardiovert AF <7 days duration. We searched MEDLINE, Embase, and CENTRAL to April 2020. The primary outcome was successful cardioversion at timepoint nearest 8 h after administration. Results: From 12 712 citations, 22 trials (2320 patients) were included. Thirteen trials included patients with some degree of heart failure; 19 included patients with some degree of ischaemic heart disease vs. placebo or rate-control (32% success) at 8 h, flecainide [73%, network odds ratio (OR) 7.6, 95% credible interval (CrI) 4.4–14.0], propafenone (70%, OR 4.6, CrI 2.9–7.3), and pilsicainide (59%, OR 10.0, CrI 1.8–69.0), but not amiodarone (28%, OR 1.0, CrI 0.4–2.8) were superior. Flecainide (OR 7.5, CrI 2.6–24.0) and propafenone (OR 4.5, CrI 1.6–13.0) were superior to amiodarone; propafenone vs. flecainide did not statistically differ (OR 0.6, CrI 0.3–1.1). At longest follow-up, amiodarone was superior to placebo (OR 11.0, CrI 3.2–41.0), flecainide vs. amiodarone (OR 0.79, CrI 0.19–3.1), and propafenone vs. amiodarone (OR 0.36, CrI 0.092–1.4) were not statistically different, and flecainide was superior to propafenone (OR 2.2, CrI 1.1–4.8). Atrial and ventricular tachyarrhythmias, bradyarrhythmias, and hypotension were rare with PO AADs. Conclusion: Single oral dose Class 1C AADs are effective and safe for cardioversion of recent-onset AF. Flecainide may be superior to propafenone. Amiodarone is a slower acting alternative.